Effect of Financial Inclusion on Small and Medium Enterprises Employment Generation in Abuja - Echendu, Peter Iheanyi; Nwekeaku , Charles; Peter, Ossai Onyeka (Kashere Journal of Politics and International Relations, 2024)
This work is aimed at x-raying the effect of financial inclusion on small and medium enterprises (SMEs) generation of employment opportunities in the Federal Capital Territory (FCT). This study explores the relationship between financial inclusion and SMEs and how it impacts employment generation in the FCT. The study examines the impact of financial inclusion on the growth and sustainability of SMEs and how this translates to employment generation in the FCT. The study employs a mixed-methods approach, combining survey and documentary data collection methods. Through a structured questionnaire, relevant data is gathered from a diverse sample of SMEs in the FCT, including information on their finances, access to credit facilities, and challenges. The findings of this study highlight the significant effect of financial inclusion on small and medium enterprises (SMEs) in the Federal Capital Territory (FCT). Secure loans, investments, and credit lines have been instrumental in supporting various aspects of SME operations, including business expansion, working capital, and investment in equipment or technology. This access to funds has played a crucial role in enabling SMEs to grow and thrive, contributing to job creation and economic development in the FCT. The study recommends that policymakers and stakeholders should prioritized financial inclusion initiatives to support SMEs and promote employment generation in the FCT